A study of risk factors for non-intentional domestic injuries among preschoolers in three suburban areas of Sri Lanka. - Liyanage, Isurujith K; Pathirana, Ashan C A; Wickramasinghe, Kremlin K; Karunathilake, Indika M; Olupaliyawa, Asela (Asia Pacific Journal of Public Health, 2008)
Unintentional injuries are common among children of Sri Lanka and globally. These can be prevented by identification and modification of risk factors. A pre-tested, structured-observation and an interview were carried out in 270 households with children less than five years in three districts. A high prevalence of risk factors for falls (58.1%), burns (51.6%), sharps injuries (51.3%), choking (65.9%) and animal-bites (53.2%) were observed. Parental identification of risk factors was less. Parents educational level significantly affected both the prevalence of risk factors (P < .05) and parental awareness (P < .05). Only 38% has received injury prevention education and the attending physician has counseled only 5% of the parents. A high prevalence of risk factors, low parental awareness and inadequate counseling by primary care physicians was noted. Primary health-care providers should be educated to encourage counseling of parents during office visits.
Keywords: risk factors; non-intentional domestic injuries; preschoolers; suburban areas; Sri Lanka